PENINGKATAN HASIL BELAJAR BERBASIS KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL PADA MATA PELAJARAN PAI DI SMP KHARISMA BANGSA KOTA TANGERANG SELATAN BANTEN - Sudrajat, Agus; Sadiyah, Rika (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2023)
This study aimed at investigating the influence of pedagogical competence and professional competence on student learning outcomes in Islamic Religious Education (IRE) at SMP Kharisma Bangsa. Pedagogical competence includes teacher skills in planning and delivering course materials effectively, while professional competence includes in-depth knowledge and understanding of the subject being taught. The researcher conducted a survey using questionnaires to be filled out by the students, the IRE teachers, and the headmaster of SMP Kharisma Bangsa. The research sample consisted of 70 respondents involved through random sampling. The collected data were analyzed using regression analysis to test the research hypothesis. The results of the study showed that pedagogical competence and professional competence significantly influenced IRE learning outcomes at SMP Kharisma Bangsa. Teachers’ pedagogical competence and professional competence respectively were found to have a significant positive contribution to IRE learning outcomes, demonstrating the importance of their ability to plan and deliver lesson material effectively and the importance of their in-depth knowledge and understanding of IRE subjects. Based on these findings, SMP Kharisma Bangsa should pay greater attention to the development of pedagogical competence and professional competence of IRE teachers. Teachers should get further training and education to improve their skills in planning and delivering lessons in an effective manner. In addition, institutional support in increasing teachers’ knowledge and in-depth understanding of the subjects of IRE is also very important. These three items should be done to significantly improve the learning outcomes of IRE at SMP Kharisma Bangsa.